Biodegradation of synthetic orange G dye by Plearotus sojar-caju with Punica granatum peal as natural mediator. (November 2019) - Bibi, Ismat; Javed, Shumaila; Ata, Sadia; Majid, Farzana; Kamal, Shagufta; Sultan, Misbah; Jilani, Kashif; Umair, Muhammad; Khan, Muhammad Iftikhar; Iqbal, Munawar
Abstract: Potential of Laccase (Lac) for the decolorization of orange G dye in the presence of natural redox mediator was investigated. Dye degradation was confirmed by Ultraviolet–visible spectroscopy (UV–Vis), High-performance liquid chromatography (HPLC) and Fourier-transform infrared spectroscopy (FTIR) techniques. Lac showed promising efficiency for the degradation of dye and redox mediator enhanced it significantly. At the Lac activity of 156.78 IU/mL, the Orange G dye was degraded up to 61.45%. The Lac activity increased significantly in the presence of Punica granatum peel extracts as a source of redox mediator and reached at 279.27 IU/mL and orange G dye decolorization was increased up to 85% and at the optimum conditions of process variables, up to 97% dye degradation was achieved. The phytotoxicity was evaluated by measuring germination of Trigonella foenum-graecum L seed in treated and untreated dye. The seed germination was inhibited 100% in untreated dye solution and germination was recorded to be 81.03% when seeds are exposed to treated dye solution. Lac ( P. sojar-caju ) in the presence of natural redox mediator ( P. granatum peal) proved to be efficient for the biodegradation of dye, which could possibly be used for the remediation of dyes in textile wastewater. Graphical abstract: Image 1 Highlights: Natural mediator extracted from P. granatum peel employed for dye degradation. Lac from P. sojar-caju were used in combination with natural redox mediator. Various process variables were optimized. Natural redox mediator showed significantly higher efficiency for dye degradation. The use of natural mediator in combination with enzymes is suggested for dyes degradation.